Manfaat Sosial Ekonomi Budidaya Sarang Burung Walet Bagi Masyarakat - Febri Erik Yudi Kha; Tonich Uda; Sri Rohaetin; Rinto Alexandro; Dehen Erang (EKONOMI & SOSIAL, 2021)
This study aims to determine and describe the socio-economic benefits of wallet bird nest cultivation for Benangin II Village, East Teweh District, North Barito Regency. This study used a qualitative approach, while in collecting data the researchers used the methods of observation, interviews, and documentation from 24 informants. As for the analysis, the author uses data collection, data reduction, data presentation, and drawing conclusions. From the results of this study it was found that swallow nest cultivation has enormous potential as a new type of business that has very large profits. But there are also swiftlet nest cultivation businesses that are successful and successful depending on how the owner of the swallow's nest building takes care to produce a lot of swallow's nests living in the building. The socio-economic benefits of bird nest cultivation for the community for the community in Benangin II Village, East Teweh District, North Barito with the assistance provided by the owners of the swallow's nest building for the community in the form of construction of alleys, renovation of places of worship, and renovation of kindergarten school buildings.